Simple machine sewing a beginner's guide to making home accessories, bags, clothes, and more - Pressley, Angela (CICO Books, 2024)
"Create 30 beautiful and useful projects with this essential guide to machine sewing. As well as being an invaluable skill and a relaxing hobby, machine sewing is a great way of being kind to the planet by upcycling scraps of fabric. Here, expert sewing teacher Angela Pressley shows you how to make 30 stunning accessories, garments, and home furnishings, each of which will help you to practice different techniques. Master topstitching, quilting, and patchwork so that you can create items for the home including a pouffe, mug cozies, and plant-pot covers. Learn how to sew curves, add pockets, and work with lightweight fabrics as you make accessories such as a bucket hat, a reversible tote, and a foldaway shopper. Finally, there’s a chapter of clothes such as a tailor-made top, a drawstring skirt, and a duster jacket, where you’ll learn how to create an elasticated hem, draft a paper pattern, and sew buttonholes. You’ll also find advice on all the tools and equipment you will need, as well as step-by-step tutorials that guide you through the machine-sewing techniques"